Solving Quadratic Equations by Completing the Square
1) Isolate the constant term 2) If the coefficient to the x2 term is not 1, divide both sides by that coefficient. 3) Complete the Square by adding the appropriate value 4) Rewrite the left side of the equation as the square of a binomial 5) Simplify
Solving Quadratic Equations by Completing the Square Example: Solve. a) x 2 + 6x – 3 = 0 x 2 + 6x = 3 x 2 + 6x + 9 = (x + 3) 2 = 12
Solving Quadratic Equations by Completing the Square Example b)3x x – 5 = 0 3x x = 5
Homework Do # 1 – 15 odd #’s only on page 170 from Section 5.7 for Friday May 15 th Don’t forget to hand in Assignment #2